2020
DOI: 10.1186/s12879-020-05048-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of a convenient detection method for Trichomonas vaginalis based on loop-mediated isothermal amplification targeting adhesion protein 65

Abstract: Background: Trichomoniasis resulting from Trichomonas vaginalis (T. vaginalis) has been considered as a commonly seen disease with the transmission way of sex. At present, the detection methods of T. vaginalis mainly include wet mount microscopy, culture, PCR, immunofluorescence and ELISA. However, all of these detection methods exist shortcomings. Methods: In this study, a loop-mediated isothermal amplification (LAMP) assay that targeted the species-specific sequence of adhesion protein 65 (AP65) gene had bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…However, in this research, we developed the RPA assay for diagnosis of T. vaginalis infection that only took 30 min to amplify the detectable amount of DNA. Moreover, the RPA assay successfully amplified T. vaginalis DNA in the temperature range of 33 to 45°C, which indicated that we can amplify the target gene by RPA using a simple heating device, such as a batterypowered heater, chemical heater, or even body heat (Lillis et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, in this research, we developed the RPA assay for diagnosis of T. vaginalis infection that only took 30 min to amplify the detectable amount of DNA. Moreover, the RPA assay successfully amplified T. vaginalis DNA in the temperature range of 33 to 45°C, which indicated that we can amplify the target gene by RPA using a simple heating device, such as a batterypowered heater, chemical heater, or even body heat (Lillis et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…These samples were examined by wet mount microscopy, culture, nested PCR, and RPA, respectively. The cultivation process of T. vaginalis was described as follows: the clinical samples (50 μl) were inoculated into fresh TYM medium and cultured in a 37°C incubator containing 5% CO 2 for 72 h. As described in our previous article (Li et al, 2020), the actin gene of T. vaginalis was amplified by nested PCR from genomic DNA. The positive rate of T. vaginalis detected by these methods was calculated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations